Atomic resolution imaging and topography of boron nitride sheets produced by chemical exfoliation - Warner, J; Rümmeli, M; Bachmatiuk, A; Büchner, B (2010)
Here, we present a simple method for preparing thin few-layer sheets of hexagonal BN with micrometer-sized dimensions using chemical exfoliation in the solvent 1,2-dichloroethane. The atomic structure of both few-layer and monolayer BN sheets is directly imaged using aberration-corrected high-resolution transmission electron microscopy. Electron beam induced sputtering effects are examined in real time. The removal of layers of BN by electron beam irradiation leads to the exposure of a step edge between a monolayer and bilayer region. We use HRTEM imaging combined with image simulations to show that BN bilayers can have AB stacking and are not limited to just AA stacking. © 2010 American Chemical Society.